Virological failure in children living with HIV on antiretroviral therapy: correlates and predictive value of clinical measurements and CD4 cell count. (October 2019) - Newman, Laura P; Pagkas-Bather, Jade; Njoroge, Anne; Wamalwa, Dalton; Nduati, Ruth; Overbaugh, Julie; Farquhar, Carey
Clinical correlates and CD4 cell count are used to predict HIV virological failure among children living with HIV in resource-limited settings, but there are limited data on their prediction of treatment failure compared to viral measurement. Using HIV viral load as a gold standard, sensitivity and specificity of longitudinal CD4 responses and clinical changes were defined in children living with HIV on antiretroviral therapy (ART) for ≥6 months in Kenya. Prevalence and correlates of virological failure were determined using log-binomial regression with robust standard error. Among 223 children who were followed for 12 months, median age in years at HIV diagnosis, ART initiation, and study enrollment were 3.3, 3.6, and 7.5, respectively. Older children at HIV diagnosis and ART initiation were less likely to experience virological failure. Immunological and clinical failure had low sensitivity (0 and 2%, respectively) to identify virological failure. Among those with virological failure, there was no indication from immunological markers and only two (2%) indicated with clinical markers. Clinical and immunological monitoring of HIV were insensitive and poor predictors of virological failure, emphasizing the importance of routine virological monitoring to inform ART treatment decisions for children living with HIV.